GRP-014 An E-Learning Programme on High-Risk Drugs – Does It Actually Increase User Knowledge?. (12th March 2013) - Creed, M; McGuirk, M; Meegan, C; Murray, D
Abstract : Background: High-risk drugs are involved in serious medicines errors. Studies have identified a range of contributory factors including lack of training. The MMU Hospital developed a E-learning programme 'A Guide to High-risk Drugs' to enable teaching; incorporating an inbuilt evaluation tool to assess the learning outcome. Purpose: To evaluate the learning from undertaking an e-learning programme on high-risk drugs. To ascertain if the programme is suitable for different types of institutions. To identify user knowledge deficits. Materials and Methods: The programme was trialled in two different hospitals. The MMUH, a 600 bed acute hospital and Peamount Hospital, a 380-bed rehabilitation and continuing care hospital. The participants were qualified Doctors, Nurses and Pharmacists. All 170 participants undertook 20 pre-assessment questions followed by the programme then the same questions in a post-assessment. Results from each institution and discipline were analysed. Results: 29 Interns completed the programme at the MMUH and 11 SHOs/Registrars in Peamount. A mean pre-assessment score of 58% (MMUH) and 56% (Peamount) increased to a post score of 83% in both hospitals. MMUH Nurses (n = 38) yielded an improvement, 48% to 73%; and Peamount Nurses (n = 40), 39% to 65%. MMUH Pharmacists (n = 20) improved from 83% to 94%. Individual questions were further analysed to ascertain if there were particular drugs causing difficulty. Analysis showed that a question on potassium chloride yielded low pre-assessment scores of 21% and 39% respectively for MMUH Doctors and Nurses and 45% and 20% for Peamount. Although both disciplines improved, this demonstrated a need for further training with this drug. Conclusions: The e-learning programme showed a significant increase in user knowledge, in both hospitals, for all disciplines. These results are very encouraging given the differences between the institutions, grades of staff and experience. The results do not stem from a 'specific teacher effect' and therefore are reproducible in multiple sites. No conflict of interest.